Hukuman Pelaku Tindak Pidana Pencabulan di Lingkungan Kampus - Basthia Surya Afifah; Teguh Suratman; Hatarto Pakpahan (Bhirawa Law Journal, 2023)
Criminal acts of obscenity are all acts related to life in the sexual field which are considered to violate the norms of decency or decency. The problem of sexual abuse on campuses or universities is no longer a secret, this is evidenced by the many reports circulating about sexual abuse in educational settings, especially universities. This study aims to find out about the judge's considerations and find out how material criminal law in Indonesia is applied to the crime of obscenity based on decision number 732 / Pid.b / 2019 / PN.Tjk, using the Normative Juridical research method. Whereas from the results of this study, the first panel of judges in deciding or adjudicating a case must make judgments by taking into account the facts of the trial, both through the statements of witnesses, expert witnesses, statements of the accused, evidence, confessions and oaths, in addition to the elements in the article. whether the accused has been fulfilled or not and also the judge's consideration must include juridical, philosophical and sociological considerations, the judge must also look at what is aggravating and what is mitigating. In decision No. 732 / Pid.b / 2019 / PN.Tjk the judge in making the decision was not fair enough and not right by trying the defendant with 1 (one) year's imprisonment. The application of material criminal law to cases of criminal acts of obscenity in the decision of the Tanjung Karang District Court Number 732/Pid. B /2019/ PN.Tjk is correct and in accordance with the applicable laws and regulations. Considering that the indictment must meet several conditions, namely formal and material requirements. The formal requirements include the defendant's biodata and the material must have a locus or place and tempo or time of incident.